Meta analisis pengaruh bahan ajar terintegrasi pendidikan berwawasan lingkungan terhadap pengetahuan peserta didik - Rahmayani, Rahmayani (Jurnal Penelitian Pembelajaran Fisika, 2020)
Educational development is an internal part of national development. National development is carried out and directed with the aim of developing quality human resources. environmental education is very important to be applied in the world of education so that the unification, attitudes and awareness of students can be increased in understanding how to protect and dilute the environment. Through teaching materials teachers will be easier to carry out learning and students will be more helped and easier to learn. This research is a meta-analytic study included in the quantitative analysis. Meta analysis of integrated teaching materials on environmentally friendly education influences students' knowledge. Integrated teaching materials on environmental education have an effect on increasing students' knowledge on environmental pollution and damage subject matter. Integrated educational teaching materials with environmental insight are more effectively applied at the level of high school education when compared to the level of junior high school education. The effect of integrated teaching materials on environmental education has a positive effect on the knowledge of students by 1.2 with a high category.